1988
DOI: 10.1016/0024-3205(88)90532-2
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic action of retinoids on gonadotropin receptor induction in rat granulosa cells in vitro

Abstract: Vitamin A (retinol) has been held to be uniquely essential for normal vision and reproduction, all other functions being served by its metabolite retinoic acid. The inability of retinoic acid to maintain adequate serum progesterone is implicated as the cause of fetal resorption. The availability of lipoproteins is a major limiting factor in progesterone production and the ovarian expression of lipoprotein receptors is dependent on the action of luteinizing hormone (LH). Therefore, we investigated the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
(24 reference statements)
2
14
0
Order By: Relevance
“…RA inhibition has previously been reported to occur in granulosa cells in association with FSH-induced LH/human chorionic gonadotropin receptor induction as well as cAMP and progesterone accumulation (Bagavandoss & Midgley 1988). In this work, RA clearly suppressed the expression of LH receptor mRNA in granulosa cells matured by FSH, as revealed by RT-PCR analysis.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…RA inhibition has previously been reported to occur in granulosa cells in association with FSH-induced LH/human chorionic gonadotropin receptor induction as well as cAMP and progesterone accumulation (Bagavandoss & Midgley 1988). In this work, RA clearly suppressed the expression of LH receptor mRNA in granulosa cells matured by FSH, as revealed by RT-PCR analysis.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the differentiation of 3T3-L1 preadipocytes is inhibited in an early stage by RA (Chawla & Lazar 1994), whereas that in Ob17 and rat preadipocytes is strongly enhanced by RA (Safonova et al 1994). In rat ovarian granulosa cells, retinoids have been reported to exert a biphasic effect on luteinizing hormone (LH) receptor induction, as revealed by a ligand-binding assay (Bagavandoss & Midgley 1988), suggesting that the response of granulosa cells to RA depends upon the stage of differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ovarian response to FSH and LH can also be modulated by RA. In response to this retinoid, stimulation of steroidogenesis (Bugavandoss & Midgley 1988, Graves-Hoagland et al 1988, and restricted expression of FSH receptor (FSHr) in rat granulosa cells has been reported (Minegishi et al 1996(Minegishi et al , 2000, which could affect oocyte growth and in turn the outcome of OPU in the cow (Argov et al 2004). In the porcine, the effects are controversial, as exposure of immature granulosa cells to RA inhibited expression of LH receptor (LHr) by downregulation of c-Fos mRNA (Hattori et al 2000).…”
Section: Embryos Transferred Pregnancy (%)mentioning
confidence: 99%
“…Increased or maintained high levels of cAMP in oocytes prevent the meiosis resumption [27]. Bagavandoss and Midgeley [28] have suggested that RA may stimulate FSH for the induction of LH receptors and also encourage progesterone production and decrease cAMP levels. Cortical granule migration as a maturation clue could be affected by RA since RA improves granular migration [29,30].…”
Section: Discussionmentioning
confidence: 99%